Pemberdayaan Remaja Sekolah dalam Memilih Pangan Aman Melalui Edukasi Bahaya Zat Aditif - M. Fadil Amirullah; Nova, Silvia; Dzulhijjah, Rahmi; Sari, Sumia Arsita (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2025)
Safe food consumption is essential for adolescent health, particularly in school environments where snacks often contain excessive food additives. The low level of student awareness regarding the risks of such additives highlights the need for education to improve literacy and decision-making in choosing safe foods. This study aims to analyze the effectiveness of food additive hazard education in empowering tenth-grade students at SMA X Pekanbaru. A pretest–posttest design was employed, involving 408 students in the pretest and 255 students in the posttest. Data were analyzed using the Shapiro–Wilk normality test, the Mann–Whitney U test, and N-Gain calculations. The results indicate a significant difference between pretest and posttest scores, although the average increase was not substantial. The N-Gain value of 0.11 is categorized as low, influenced by the students’ initially high baseline scores and possible fatigue during the educational session, which caused some scores to decrease. Nevertheless, the educational intervention positively impacted students’ knowledge and awareness of food additive hazards. In conclusion, the intervention effectively strengthened students’ understanding and empowerment in selecting safe foods, although more interactive learning strategies are recommended to optimize outcomes.